THE INFLUENCE OF EMPLOYEES’ COMPETENCY AND ORGANIZATIONAL SUPPORT TOWARD EMPLOYEES’ PERFORMANCE IN PRODUCTION DEPARTMENT OF PT CEGE ONE SEMARANG - Lina Ilfa Zakhiyatus Sa’adah; Jozef Bambang Trijoga; Yuli Sudarso (JOBS (Jurnal Of Business Studies), 2017)
The purpose of this research is to analyze the influence of employees’ competency and organizational support toward employees’ performance in production department of PT CEGE ONE Semarang. This research uses multiple linear regression. There are 70 respondents participated in this research who given the questionnaire, the sampling technique is using proportionate stratified random sampling. The methods of data collection are observation, questionnaire, interview, and documentation studies. The result shows that analysis which is carried out by SPSS 16. The result shows that employees’ competency and organizational support has significant positive influenced toward employees’ performance. The contribution of employees’ competency and organizational support toward employees’ performance is 16.2 % and the rest 83.8 % is affected by other variables that aren’t observed in this research.